A general model of bank decisions - Broaddus, Alfred (USA : Federal Reserve Bank of Richmond, 1972)
This paper presents a general theoretical model of individual bank balance sheet management under conditions of uncertainty.
Preliminary: not to be quoted
Includes bibliographical references
osc 26/04/17
Loans
Keywords: Banks